LABORATORY DIAGNOSIS OF HEREDITARY DISEASES: A REVIEW OF MODERN METHODS AND THEIR CLINICAL SIGNIFICANCE (International Conference on Economics, Finance, Banking and Management, 2025)
Hereditary diseases are a group of pathologies caused by mutations in the genetic material transmitted by inheritance. Timely and accurate laboratory diagnosis of such diseases is crucial for early intervention, prognosis and genetic counselling. This review article focuses on modern methods of laboratory diagnosis of hereditary diseases, including molecular genetic, biochemical and cytogenetic approaches, and their integration into clinical practice [5,6,7].